The Correlation Between Survival Benefit of Preoperative Radiotherapy and Pretreatment Carcinoembryonic Antigen Level in Locally Advanced Rectal Cancer - Wang, Lei; Zhong, Xiaohong; Lin, Huaqin; Shao, Lingdong; Chen, Gang; Wu, Junxin (Frontiers in Oncology, 2021)
Background: Preoperative radiotherapy followed by radical surgery is the standard treatment for locally advanced rectal cancer, however, its long-term survival benefit remains controversial. This study aimed to determine the relationship between pre-treatment carcinoembryonic antigen (CEA) levels and the long-term prognosis of preoperative radiotherapy in LARC patients. Methods: Data of LARC patients who underwent surgery between 2011 and 2015 were identified from the Surveillance, Epidemiology, and End Results (SEER) database, and patients were accordingly divided into surgery (S) group and radiotherapy followed by surgery (RT+S) group. The primary outcomes were cancer specific survival (CSS) and cancer specific mortality (CSM). CSS was evaluated using Kaplan-Meier analysis, while CSM was evaluated using a competitive risk model. Subgroup analysis was also conducted, which was stratified by pre-treatment CEA levels. Results: A total of 2760 patients were eligible for this study, including 350 (12.7%) patients in the S group and 2410 (87.3%) in the RT+S group. There were no significant differences in the CSS and CSM rates at 1, 3, and 4-years between the S and RT+S groups before and after PSM (all P>0.05). Pre-treatment CEA levels were independently associated with CSS and CSM after adjusting for age, sex, stage, pathological factors, and treatment factors (all P<0.05). Subgroup analysis showed that preoperative radiotherapy would benefit patients with elevated CEA in terms of CSS and CSM (both P<0.05) but not those patients with normal CEA (both P>0.05). Further analysis showed that preoperative radiotherapy was an independent protective factor for CSS and CSM in patients with elevated CEA levels (both P<0.05). Conclusions: Pre-treatment CEA level may be considered a potential biomarker to screen LACR patients who would benefit from preoperative radiotherapy in terms of long-term prognosis.